2016
DOI: 10.15567/mljekarstvo.2016.0405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of packaging materials on some ripening characteristics of Tulum cheese

Abstract: In this study the effects of different packaging materials on Tulum cheese made with cloth, stomach, animal skin, pot and plastic materials were investigated. Dry matter, ash, titratable acidity, salt, salt in dry matter, fat, total protein, water soluble nitrogen (WSN), trichloroacetic acid soluble nitrogen (TCA-SN), phosphotungstic acid soluble nitrogen (PTA-SN), electrophoretic casein fraction analyses, L*, a* and b* values in colour analyses and sensory characteristics were analysed. Dry matter 54.74-66.37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
(18 reference statements)
2
10
0
1
Order By: Relevance
“…Deegan et al . () and Tarakci and Durmuş () similarly reported that the L * values decreased during storage. The decrease in L * value over time was associated with the water loss in the samples, partial oxidation during storage period and the increase in microorganism counts in the samples (Tomar et al .…”
Section: Resultsmentioning
confidence: 78%
“…Deegan et al . () and Tarakci and Durmuş () similarly reported that the L * values decreased during storage. The decrease in L * value over time was associated with the water loss in the samples, partial oxidation during storage period and the increase in microorganism counts in the samples (Tomar et al .…”
Section: Resultsmentioning
confidence: 78%
“…Accordingly, the Tulum cheese samples are under the category of less ripened cheese. Tarakci & Durmuş (2016) determined that the ripening index values of the cheeses ripened in skin and plastic materials were higher than those ripened in cloth, animal stomach and pot materials. Yasar (2007) and Gun (2012) stated that the ripening index increased for the cheeses that were stored time.…”
Section: Resultsmentioning
confidence: 99%
“…The increase of L* values in vacuum packed cheese samples was believed to be caused by not losing water in the package during the storage period resulting in conservation of the initial white colour during the storage period. [49] In their work, Tarakçı and Durmuş [50] studied effects of packaging materials on colour of cheese and found that plastic packaging material caused higher L* values of the cheese. Their findings correspond to our measurements of colour changes during storage of BN, BP and BM bryndza cheese varieties.…”
Section: Parameter Storagementioning
confidence: 99%
“…Proteolysis is probably the most important biochemical event having a major impact on flavour and texture of most cheese varieties. [50] In each bryndza cheese variety (BN, BP with addition of cow lump cheese from pasteurised milk (50%); BS, before storage; NP, after the 14 th day of storage without packaging; VP, after the 14 th day of vacuum packaging storage; V, the main effect of bryndza cheese variety; S, the main effect of storage in vacuum-and non-vacuum-packed bryndza cheese samples; V × S, interaction effect between varieties and storage; A-C , in a column means (storage conditions) without a common superscript letter differ (p < 0.05); a-c , in a row means (cheese variety) without a common superscript letter differ (p < 0.05). BU, bryndza cheese made from unpasteurised ewe milk; BP, bryndza cheese made from pasteurised ewe milk; BM, bryndza cheese made from unpasteurised ewe milk with addition of cow lump cheese from pasteurised milk (50%); BS, before storage; NP, after the 14 th day of storage without packaging; VP, after the 14 th day of vacuum packaging storage; V, the main effect of bryndza cheese variety; S, the main effect of storage in vacuum-and non-vacuum-packed bryndza cheese samples; V × S, interaction effect between varieties and storage; A-C , in a column means (storage conditions) without a common superscript letter differ (p < 0.05); a-c , in a row means (cheese variety) without a common superscript letter differ (p < 0.05).…”
Section: Parameter Storagementioning
confidence: 99%